English Instructor for Adult Learners at PARI MATCH company (appointed by CUT) - Christoforou, Maria (My University, 2026)
- Teaching "Business English" to adults at PARIMATCH company, appointed by the Cyprus University of Technology. The lessons include incorporating the use of: - Google Drive, - YouTube, - SlideShare, - Kahoot, - Padlet - Mentimeter -Ted Talks as well as the use of authentic material, based on needs analysis.